The origin of the notion of the archaeological monument in Polish law - Artemiuk, Jakub (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
This article aims to give an insight into the genesis of the notion of the archaeological monument in Polish law. The study focuses primarily on quoting and comparing the definitions that have appeared over the years in various legal acts regulating the issue of protection of archaeological heritage in Poland and included in its scope archaeological monuments. It takes into consideration Polish laws enacted since 1918 until the present day as well as the European Convention on the Protection of the Archaeological Heritage (Revised), which is an example of an international agreement that contains a legal definition of the archaeological monument and is directly applicable in Poland. This paper aims to show how the archaeological monuments have been described in Polish law and how the legal concept of the archaeological monument has evolved from the first casuistic, descriptive terminology to the contemporary synthetic and quite precise definition of the archaeological monument.
Keywords: definition of the archaeological monument; law & archaeology; archaeological monument; history of law; protection of monuments